Preliminary study of the statistical content orientation during the formation process of the Physical culture professional/Estudio preliminar de la orientación del contenido estadístico durante el proceso de formación del profesional de Cultura Física - Enilda Mariselis Jorrin Carbó; Danay Quintana Rodríguez; Juan Gustavo Kessel Rodríguez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The study of the Statistic as a discipline on majoring at Physical Culture has a great importance for its application in scientific research and its high impact in the fields of professional performance, besides the scientific contribution to the Cuban sport movement. For these reasons the study of the statistical content should be considered to express a widespread interpretation from the different sciences. The objective of the research was to value the orientation of the study of the statistic, from the use of the interdisciplinary cores, during the process of professional formation in students of Physical Culture. During the research process it was necessary the use of empiric methods as the document review, the survey, the interview and the observation, besides, the methodological triangulation as confirmation tool. It is intended as possible solution to transform the reality achieved during the carried out diagnosis, the design of a methodological strategy to favor the teaching and learning of the statistical content in students of Physical Culture.